High-melting-point crystals of poly(l-lactic acid) (PLLA): the most efficient nucleating agent to enhance the crystallization of PLLA1. Issue 11 (21st March 2015) - Yin, Hai-Yan; Wei, Xin-Feng; Bao, Rui-Ying; Dong, Quan-Xiao; Liu, Zheng-Ying; Yang, Wei; Xie, Bang-Hu; Yang, Ming-Bo
<x xml:space="preserve">Abstract</x> Self-nucleation theory is employed to enhance polymer crystallization in practical processing techniques by introducing high-melting-point crystals.